WebSphere Commerce Portal V5.4 solutions : integrating WebSphere Commerce V5.4, business edition and WebSphere Portal V4.2 - Ganci, John (IBM redbooks., 2003)
Portals provide the user with a single point of access to a wide variety of content, data and services throughout an enterprise. The content displayed in portlets on the portal page can be personalized based on user preferences, site design and marketing campaigns. IBM WebSphere Commerce Portal provides an integrated solution for aggregating and personalizing commerce content and data by leveraging the technologies of WebSphere Commerce V5.4 and WebSphere Portal V4.2. When using the WebSphere Commerce Portal, users have a single point of access to personalized content in portlets from Web browser clients and mobile devices. This IBM Redbooks publication provides an overview of the WebSphere Commerce Portal benefits, features and architecture. The focus of the book is an end-to-end working example scenario for a commerce enabled portal B2B store. The working example includes the following topics; business requirements analysis and solution design, multi-tiered runtime implementation procedures, development environment with source level debug of commerce portlets and JSPs, create a commerce enabled portal store using WebSphere Studio Application Developer, create Dynamic Context Groups, and mobile client access. Please note that the additional material referenced in the text is not available from IBM.